A Facile Synthesis of Co3O4 Hollow Microtubes by Decomposition of a Cobalt Metal–Organic Framework. Issue 27 (4th July 2016) - Gómez‐Aguirre, L. Claudia; Castro‐García, Socorro; Sánchez‐Andújar, Manuel; Yáñez‐Vilar, Susana; Mira, Jorge; Bermúdez‐García, Juan Manuel; Centeno, Teresa A.; Señarís‐Rodríguez, María Antonia
Abstract : In this work, we have successfully synthesized hollow microtubular crystals of the metal–organic framework (MOF) [Co2 (NH2 ‐bdc)2 (dabco)]· [G] G = H2 O, N, N ‐dimethylformamide (DMF); NH2 ‐bdc =2‐amino‐1, 4‐benzenedicarboxylate; dabco = 1, 4‐diazabicyclo[2.2.2]octane by a very simple coordination‐modulation method that avoids the use of an external modulator. Additionally, we have obtained the corresponding hollow microtubular crystals of Co3 O4 through the solid‐state thermolysis of the Co‐MOF material at 400 °C. The as‐prepared Co3 O4 crystals exhibit the typical magnetic behavior for a nanostructured material with good crystallinity. Thus, this coordination‐modulation method provides a simple route for the preparation of nanostructured porous frameworks and derived oxides and opens a way to prepare new materials with advanced properties. Abstract : We obtained the metal–organic framework [Co2 (NH2 ‐bdc)2 (dabco)]· [G] G = H2 O, N, N ‐dimethylformamide; NH2 ‐bdc = 2‐amino‐1, 4‐benzenedicarboxylate; dabco = 1, 4‐diazabicyclo[2.2.2]octane as hollow microtubes and synthesized microtubular crystals of Co3 O4 by calcination at 400 °C. The coordination‐modulation method provides a simple route to nanostructured porous frameworks and derived oxides.